Organization of the IWS on the course of physics under conditions technical university - Nauryzbayeva, G.; Gabdullina, G.L. (Recent Contributions to Physics, 2022)
The article outlines ways to improve the organization of independent work of university students. Innovative education is the use of the latest information technologies in the entire didactic complex of information support for the subject. The innovative model of teaching physics in higher education includes methodologically structured information presented in the form of one of the types of the infosphere - a system of interrelated and interdependent textbooks and other means of educational activity (modular programs, electronic lectures, various methodological aids). In the new conditions of increasing the volume and strengthening the role of students' independent work in the educational process, students receive and master only methodological information at the appropriate level. To master the material on a regular basis, a student needs to work for months, and only a qualified teacher who knows the psychological characteristics of the learning process and owns the teaching methodology will help save the student's time by transforming the professional knowledge of teachers into educational knowledge. The paper shows the types and stages of performing classroom, extracurricular IWS in physics, as well as ways to improve the efficiency and quality of students' educational work.